Calculation of critical inductance in n‐input buck dc–dc converter. Issue 12 (1st October 2016) - Babaei, Ebrahim; Varesi, Kazem; Vosoughi, Naser
Abstract : This study investigates a multiple input buck dc–dc converter. Different operational modes of the converter for two‐, three‐ and four‐input sources are studied then, for each item the relation of critical inductance between continuous conduction mode and discontinuous conduction mode is calculated. Finally, a generalised relationship is proposed for calculation of critical inductance of n ‐input topology, which is true for any number of input sources. Experimental and simulation results in power systems computer‐aided design/EMTDC are presented to validate the theoretical concepts and proposed generalised relation of converter critical inductance.